Lopinavir/ritonavir as a third agent in the antiviral regimen for SARS-CoV-2 infection. (27th April 2021) - Panagopoulos, Periklis; Petrakis, Vasilis; Panopoulou, Maria; Trypsianis, Grigorios; Penlioglou, Theano; Pnevmatikos, Ioannis; Papazoglou, Dimitrios
Abstract: Corona Virus Disease (CoVID-19) is an emerging public health problem rapidly spread globally. New treatment options for patients with severe symptoms and ways of reducing transmission in the community are taken into consideration. A retrospective study was conducted in the Department of Infectious Diseases of Alexandroupolis (Greece) including 16 patients with CoVID-19. They were classified into two groups, A and B. Group A received lopinavir/ritonavir as a third agent in the antiviral regimen, while group B did not. Lymphocytes were more significantly increased in patients of group A. Ferritin serum levels were also decreased significantly in these patients. Number of days needed for a first negative result of Real Time- Polymerase Chain Reaction (RT-PCR) was lower for Group A. The present study suggests that lopinavir/ritonavir may reduce the viral carriage in a shorter period of time compared with other antiviral regimens. Further studies are needed in order to evaluate the effectiveness of lopinavir/ritonavir in the treatment of patients with SARS-CoV-2 infection.